TOURISM SECTOR DEVELOPMENT OF BARRIERS: TERRORISM - Sadık SERÇEK (Fırat University, 2019)
Advances in technology, increased travel and changing world order, terrorism, it has become one of the world's most experienced and serious international problem. Terrorism, always ahead of the national and international which is highly complex and changing phenomenon. In this study, the tourism industry and the concept of terrorism as obstacles to the development of tourism are analyzed. Terrorism and tourism relations with the relevant literature scanning the tourism sector impacts on terrorism, the destination image influence on terrorism, in particular in the Southeastern Anatolia terrorism and put forward various aspects such as the fight against terrorism paths. According to data from 2009-2014, which operates in the Southeastern Anatolia Region tourism businesses of terrorism and its impact on the number of tourists staying in the municipality certified facilities were examined. In addition, estimates made in 2015 and 2020, terrorism has been put out to affect how data for 2015. Turkey Statistics Institute and the Culture and Tourism Ministry obtained has examined dealt with trend analysis of numerical prediction method. Since 2009 the increase in the number of tourists in the coming tourism until 2013 but reached the conclusion not reached the expected number. Data for 2013 has been reached on the expected number of visitors is examined. This increase in the "Resolution Process" domestic tourists of the start of the ceasefire in the Southeastern Anatolia Region is seen as more checks. Not reached the estimated number in 2014; In 2015 2.273.357 tourists arrival is assumed to be. However, since the middle of 2015. From the end of 2015 with the arrival of the threshold can not be reached, it said the solution process the expected number. As a result, the Southeast Anatolia terrorism, has been found to have negative effects on investments, agriculture, tourism sector and social structures.